High-performance wave-absorbing material based on carbonyl iron and nanocrystalline and preparation method of high-performance wave-absorbing material

By mixing carbonyl iron with special nanocrystals in a specific proportion and combining with resin to form a high-performance absorbing material, the shortcomings of existing absorbing materials in the absorbing frequency band, absorption efficiency and environmental adaptability are solved, and the goals of wide-band and efficient absorption and environmental protection are achieved.

CN119662087APending Publication Date: 2025-03-21HANGZHOUSNNER MACHINERY EQUIP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411922045.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing absorbing materials have shortcomings in the absorption frequency band, absorption efficiency and environmental adaptability, which are difficult to meet the demand of modern electronic technology for high-performance absorbing materials.

Method used

A high-performance absorbing material based on carbonyl iron and nanocrystals is used to form a composite coating of absorbing material powder and resin by mixing carbonyl iron and nanocrystals in a specific proportion and combining it with the resin. Nanocrystals are obtained by fast quenching and tempering treatment, and have hysteresis loops close to rectangular shapes.

Benefits of technology

It realizes efficient wave absorption in a wide frequency range, significantly improves the absorbing performance of the material, and the comprehensive density of the material is low, meets environmental protection requirements, simplifies process, is easy to produce on a large scale, and is widely used in aerospace, electronic equipment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662087A_ABST
    Figure CN119662087A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance wave-absorbing material based on carbonyl iron and nanocrystalline and a preparation method thereof.The wave-absorbing material comprises wave-absorbing material powder and resin, the weight part ratio of the wave-absorbing material powder to the resin is 100: 80-90, the wave-absorbing material powder comprises carbonyl iron and nanocrystalline, the weight part ratio of the nanocrystalline to the carbonyl iron is 7-11: 3-9, the nanocrystalline is composed of iron, silicon, niobium, boron and copper according to the proportion, and the weight ratio of iron to silicon to niobium to boron to copper is 73.5-79: 12-13.5: 1-3: 7-9: 1-2, so that the nanocrystalline has a hysteresis loop close to a rectangle. The preparation method has the beneficial effects that the advantages of carbonyl iron and nanocrystalline are combined, efficient wave absorption in a broadband range is realized, and the wave absorption performance of the material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technology of wave absorbing materials in the field of material science, and mainly relates to a high-performance wave absorbing material based on carbonyl iron and nanocrystals and a preparation method thereof. Background Art

[0002] With the rapid development of modern electronic technology, electromagnetic wave pollution and stealth technology have become hot topics in the current scientific research field. However, traditional absorbing materials still have obvious deficiencies in terms of absorbing frequency band, absorption efficiency and environmental adaptability. For example, Chinese patent CN103073961A discloses a multi-component composite absorber, absorbing coating, absorbing substrate and preparation method. The absorber is composed of ACET, α-SiC, and Ni0.7Zn0.3Fe2O4 in weight ratio; the absorbing coating is composed of the aforementioned absorber, deionized water, PVA solution, wetting agent, dispersant, defoaming agent, and water-based leveling agent in weight ratio; the absorbing substrate includes several pyramidal substrates coated with the aforementioned absorbing coating on both sides. Therefore, the development of new high-performance absorbing materials with high efficiency, wide frequency response, light weight and strong environmental adaptability has become an important direction of current materials science research. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a high-performance microwave absorbing material based on carbonyl iron and nanocrystals and a preparation method thereof.

[0004] The objective of the present invention is achieved through the following technical scheme: A high-performance wave-absorbing material based on carbonyl iron and nanocrystals, the wave-absorbing material comprises wave-absorbing material powder and resin, the weight ratio of the wave-absorbing material powder and the resin is 100:80-90, the wave-absorbing material powder comprises carbonyl iron and nanocrystals, the weight ratio of the nanocrystals and the carbonyl iron is 7-11:3-9, wherein the nanocrystals are composed of iron, silicon, niobium, boron and copper in proportion, the weight ratio of iron: silicon: niobium: boron: copper is 73.5-79:12-13.5:1-3:7-9:1-2, so that the nanocrystals have a hysteresis loop close to a rectangle.

[0005] As a preferred technical solution, the nanocrystals are composed of iron, silicon, niobium, boron and copper in proportion, with the weight percentages of iron: silicon: niobium: boron: copper being 73.5%, 13.5%, 3%, 9% and 1% respectively; the particle size of carbonyl iron is 5-8 microns, and the particle size of nanocrystals is 250 mesh.

[0006] As a preferred technical solution, the resin includes phenolic resin and fluorocarbon resin.

[0007] The present invention also provides a method for preparing a high-performance wave absorbing material based on carbonyl iron and nanocrystals, comprising the following steps:

[0008] Step 1, ingredients: according to the preset total amount and proportion, accurately weigh carbonyl iron with a particle size of 5-8 microns and 250 mesh nanocrystals, and place them in a stainless steel plate for later use;

[0009] Step 2, dehumidification: Place the container containing the powder in an oven and dry it at 80 degrees Celsius for 60 minutes to completely remove the moisture in the material;

[0010] Step 3, mixing: the resin is mixed with carbonyl iron and nanocrystalline powder in a certain proportion, and then poured into a mixing barrel;

[0011] Step 4: Dispersion: Use a stirrer to disperse the mixture and stir for 45 minutes to ensure that all components are evenly mixed to form a uniform absorbing coating material;

[0012] Step 5: Coating and curing: The prepared absorbing coating material is evenly coated on the aluminum plate by spraying or brushing, and then placed in an oven and dried at 70 degrees Celsius for 60 minutes to complete the curing process.

[0013] The nanocrystals are obtained by rapid quenching and tempering, including the following steps:

[0014] Step 1, smelting: according to the ratio, accurately weigh the raw materials of iron, silicon, niobium, boron and copper, add the weighed raw materials into the rapid quenching furnace in order, and carry out high-temperature smelting to ensure that all elements are fully integrated;

[0015] Step 2, rapid quenching treatment: using the rapid cooling of the rapid quenching furnace, the molten metal liquid is quickly cooled to a solid state to form an amorphous structure; the cooling rate is controlled, when the molten metal liquid is cooled, the atoms or molecules do not have time to arrange according to the conventional crystalline structure, thus forming a disordered, amorphous solid structure;

[0016] Step 3, making a strip and winding ring: the alloy material after rapid quenching is processed through a specific strip making process to prepare an amorphous alloy strip of a desired shape, and then sent to a winding machine to wind the amorphous strip into an amorphous ring;

[0017] Step 4, heat treatment: at the crystallization temperature, the atoms or molecules inside the amorphous ring gain energy, and are rearranged to transform the amorphous structure into nanocrystals, so that the material obtains a hysteresis loop close to a rectangle; the heat treatment method is as follows: first, the temperature must be selected within the crystallization temperature range of the material; second, the tempering time must be sufficient to rearrange the atoms or molecules from the amorphous state to the crystalline structure; finally, the amorphous ring is oriented in the tempering furnace, and the furnace door is closed and vacuumed; at the beginning of heating, the coil of the tempering furnace is powered on to form a magnetic field perpendicular to the radial direction of the amorphous ring; after the furnace temperature rises to the crystallization temperature, it is kept warm for 1 hour, and then all power supplies of the tempering furnace are turned off and naturally cooled to room temperature before being taken out of the furnace; the nanocrystalline rings after being taken out of the furnace are crushed, ball-milled, and sieved to obtain nanocrystalline powder.

[0018] The beneficial effects of the present invention are:

[0019] 1. High-efficiency wave absorption: Combining the advantages of carbonyl iron and nanocrystals, high-efficiency wave absorption in a wide frequency range is achieved, significantly improving the wave absorption performance of the material.

[0020] 2. Lightweight and environmentally friendly: The two complement each other, making the overall density of the material low and free of substances harmful to the human body, which fully meets environmental protection requirements.

[0021] 3. Process simplification: As long as the raw materials are strictly screened and tested to ensure the quality of the raw materials, the preparation process will be relatively simple, without the need for heavy equipment investment, and it is easy to achieve large-scale production.

[0022] 4. Wide application: This material can be widely used in aerospace, electronic equipment, communication base stations and other fields, with broad market prospects and huge economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a curve diagram of the reflection loss of the absorbing material of Example 1 of the present invention.

[0024] Figure 2 This is a curve diagram of the reflection loss of the absorbing material of Example 2 of the present invention. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with the accompanying drawings and specific embodiments. However, it should be understood that the accompanying drawings are only for illustrative purposes and cannot be understood as limiting the present invention. In order to better illustrate the present embodiment, some parts of the accompanying drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the accompanying drawings may be omitted. The positional relationship described in the accompanying drawings is only for illustrative purposes and cannot be understood as limiting the present invention.

[0026] The invention provides a high-performance wave-absorbing material based on carbonyl iron and nanocrystals, which is a high-performance composite wave-absorbing material that combines carbonyl iron and special nanocrystal materials. The wave-absorbing material includes wave-absorbing material powder and resin, the weight ratio of the wave-absorbing material powder and the resin is 100:80-90, the wave-absorbing material powder includes carbonyl iron and nanocrystals, the weight ratio of nanocrystals and carbonyl iron is 7-11:3-9, and the ratio range of nanocrystals to carbonyl iron can be adjusted according to specific application requirements, generally varying between 30% and 70%. The specific ratio needs to consider factors such as the magnetic properties, mechanical properties and processing properties of the material. Among them, the nanocrystals are composed of iron, silicon, niobium, boron and copper in proportion, and the weight ratio of iron: silicon: niobium: boron: copper is 73.5-79:12-13.5:1-3:7-9:1-2, so that the nanocrystals have a hysteresis loop close to a rectangle.

[0027] Wave absorption mechanism: Carbonyl iron: With its excellent electromagnetic properties such as high magnetic permeability and low resistivity, it has become an ideal raw material for preparing wave-absorbing materials. Nanocrystals are mainly composed of: metal nanocrystals and metal oxide nanocrystals. The nanocrystals used in the present invention are metal nanocrystals. Nanocrystals: are made of iron, silicon, niobium, boron, and copper elements through precision smelting, rapid quenching, and longitudinal magnetic furnace crystallization. Their unique rectangular hysteresis loop and ultra-high magnetic permeability significantly enhance the material's magnetic loss capacity, which is a key factor in improving wave absorption performance. The wave-absorbing material of the present invention achieves an organic combination of the three mechanisms of magnetic loss, electrical loss, and dielectric loss through the precise compounding of carbonyl iron and nanocrystals, thereby achieving efficient absorption of electromagnetic waves. The electromagnetic properties of carbonyl iron and the ultra-high magnetic permeability of nanocrystals work in synergy, significantly enhancing the material's wave absorption ability over a wide frequency range.

[0028] Example 1: The nanocrystal (high magnetic permeability type) is composed of iron, silicon, niobium, boron and copper in a proportion, and the weight percentages of iron: silicon: niobium: boron: copper are 73.5%, 13.5%, 3%, 9% and 1% respectively. The particle size of carbonyl iron is 5-8 microns, and the particle size of nanocrystal is 250 mesh. Nanocrystal accounts for 55%, and carbonyl iron (5-8um spherical) accounts for 45%. Under this ratio, the obtained Figure 1 Reflectivity test curve shown.

[0029] Example 2: The difference from Example 1 is that nanocrystals account for 70% and carbonyl iron accounts for 30%. Under this ratio, the obtained Figure 2 Reflectivity curve: It can be seen from the figure that the frequency of the absorption peak point increases slightly, and the absorption bandwidth at -10dB becomes significantly narrower.

[0030] As a preferred technical solution, the resin includes phenolic resin and fluorocarbon resin.

[0031] The present invention also provides a method for preparing a high-performance wave absorbing material based on carbonyl iron and nanocrystals, comprising the following steps:

[0032] Step 1, ingredients: according to the preset total amount and proportion, accurately weigh carbonyl iron with a particle size of 5-8 microns and 250 mesh nanocrystals, and place them in a stainless steel plate for later use;

[0033] Step 2, dehumidification: Place the container containing the powder in an oven and dry it at 80 degrees Celsius for 60 minutes to completely remove the moisture in the material;

[0034] Step 3, mixing: select a resin with a suitable dielectric constant and excellent weather resistance, mix it with carbonyl iron and nanocrystalline powder in a certain proportion, and then pour it into a mixing barrel;

[0035] Step 4: Dispersion: Use a stirrer to disperse the mixture and stir for 45 minutes to ensure that all components are evenly mixed to form a uniform absorbing coating material;

[0036] Step 5: Coating and curing: The prepared absorbing coating material is evenly coated on a 300*300*4 mm aluminum plate by spraying or brushing, and then placed in an oven and dried at 70 degrees Celsius for 60 minutes to complete the curing process.

[0037] Preparation method of nanocrystals

[0038] The preparation methods of nanocrystals include: gas phase method, liquid phase method, solid phase method, chemical method, electrochemical method, rapid quenching method, etc. The nanocrystals described in the present invention are obtained by rapid quenching method plus tempering treatment.

[0039] Complete process

[0040] 1. Melting:

[0041] 1.1 Raw material preparation: Accurately weigh the raw materials of iron, silicon, niobium, boron and copper according to the ratio.

[0042] 1.2 Melting equipment: Rapid quenching furnace is used as the main melting equipment.

[0043] 1.3 Melting process: Add the weighed raw materials into the rapid quenching furnace in order and carry out high-temperature melting to ensure that all elements are fully integrated.

[0044] 2. Rapid quenching treatment:

[0045] 2.1 Rapid quenching technology: Using the rapid cooling technology of the rapid quenching furnace, the molten metal liquid is quickly cooled to a solid state to form an amorphous structure.

[0046] 2.2 Cooling rate: Control the cooling rate within a very high range (such as greater than 10^6℃ / S). When the molten metal liquid cools at a very fast speed, the atoms or molecules do not have time to arrange themselves according to the conventional crystalline structure, thus forming a disordered, amorphous solid structure. This amorphous structure is manifested as an irregular arrangement of atoms or molecules at the microscopic level, without long-range order.

[0047] 3. Making belt reel ring:

[0048] 3.1 Strip making process: The alloy material after rapid quenching is processed through a specific strip making process to prepare an amorphous alloy strip of the desired shape, and then sent to a winding machine to wind the amorphous strip into an amorphous ring.

[0049] 4. Heat treatment:

[0050] 4.1 Purpose of heat treatment: First, at the crystallization temperature, the atoms or molecules inside the amorphous ring gain energy and rearrange the amorphous structure to transform it into nanocrystals, so as to improve the magnetic permeability of the product and reduce the coercive force. The most critical point is to make the material obtain a hysteresis loop close to a rectangle (this is the key to the material being able to prepare high-performance absorbing materials).

[0051] 4.2 Heat treatment method: First, the temperature must be selected within the crystallization temperature range of the material (600°-650°). Second, the tempering time must be sufficient to reorder the atoms or molecules from the amorphous state to the crystalline structure. Finally, after the amorphous ring is oriented in the tempering furnace, the furnace door is closed and the vacuum is evacuated to about 100P. At the beginning of heating, the coil of the tempering furnace is powered on to form a magnetic field (about 1000GS) perpendicular to the radial direction of the amorphous ring. After the furnace temperature rises to the crystallization temperature, keep it warm for 1 hour, then turn off all the power of the tempering furnace and cool it naturally to room temperature before it can be taken out of the furnace.

[0052] 4.3. Post-processing: The nanocrystalline rings are crushed, ball-milled and sieved after being taken out of the furnace. Finally, nanocrystalline powder with a size of less than or equal to 250 mesh is obtained.

[0053] Requirements for resins in preparing radar-absorbing coatings:

[0054] 1. Transparency: The resin must be transparent in the infrared and radar bands to ensure that the absorbing powder can effectively absorb and reduce reflection.

[0055] 2. Dielectric properties: Good dielectric properties help the resin and the absorbing powder to form a good interface bond and improve the overall absorbing effect of the coating.

[0056] 3. Mechanical properties: The resin should have good mechanical properties, such as tensile strength, compressive strength, etc., to ensure that the coating can adhere firmly to the aircraft surface and withstand various mechanical impacts during flight.

[0057] 4. Thermal properties: The resin should be able to withstand the high temperatures generated by the aircraft when flying at high speeds and maintain the stability and durability of the coating.

[0058] 5. Chemical stability: The resin should have good chemical stability and be able to resist the corrosion of various chemical substances to ensure that the coating will not deteriorate or fail during long-term use.

[0059] The resin used in the present invention mainly consists of the following two types:

[0060] 1. Phenolic resin (ammonium chloride is used as curing agent)

[0061] 2. Fluorocarbon resin (hexamethylene diisocyanate is selected as the curing agent).

[0062] The weight ratio of the absorbing material powder (nanocrystalline + carbonyl iron) to the resin is between 100:80 and 100:90. Add 5% WT thinner for brushing (stir in a mixer for 30 minutes) and 20% WT thinner for spraying (stir for 30 minutes). Usually, "thinner" is used as a thinner for phenolic resin. Fluorocarbon resin can use a special thinner for fluorocarbon paint.

[0063] Test results:

[0064] After strict testing, the absorbing material of the present invention exhibited excellent absorbing performance when the coating thickness of the sample was 0.91 mm. The reflection loss curve clearly showed that the material had significant absorbing effects in multiple frequency bands. Figure 1 In order to reflect the reflection loss curve of the absorbing material in the test report, the reflectivity test results of the coating material at 2-38GHz show the absorbing performance of the material in detail.

[0065] The present invention makes full use of the excellent electromagnetic properties of carbonyl iron and the unique rectangular hysteresis loop and ultra-high magnetic permeability of nanocrystals to achieve efficient and broadband electromagnetic wave absorption. At the same time, the present invention also optimizes the preparation process in order to improve the environmental adaptability of the material.

[0066] It is understandable that, for those skilled in the art, any equivalent replacement or change to the technical solution and inventive concept of the present invention should fall within the protection scope of the claims attached to the present invention.

Claims

1. A high-performance microwave absorbing material based on carbonyl iron and nanocrystals, characterized in that: The absorbing material comprises absorbing material powder and resin, the weight ratio of the absorbing material powder and the resin is 100:80-90, the absorbing material powder comprises carbonyl iron and nanocrystals, the weight ratio of the nanocrystals and the carbonyl iron is 7-11:3-9, wherein the nanocrystals are composed of iron, silicon, niobium, boron and copper in proportion, the weight ratio of iron: silicon: niobium: boron: copper is 73.5-79:12-13.5:1-3:7-9:1-2, so that the nanocrystals have a hysteresis loop close to a rectangle.

2. The high-performance microwave absorbing material based on carbonyl iron and nanocrystals according to claim 1, characterized in that: The nanocrystals are composed of iron, silicon, niobium, boron and copper in proportion, with the weight percentages of iron: silicon: niobium: boron: copper being 73.5%, 13.5%, 3%, 9% and 1% respectively; the particle size of carbonyl iron is 5-8 microns, and the particle size of nanocrystals is 150-250 meshes.

3. The high performance microwave absorbing material based on carbonyl iron and nanocrystals according to claim 1, characterized in that: The resin includes phenolic resin and fluorocarbon resin.

4. A method for preparing a high-performance microwave absorbing material based on carbonyl iron and nanocrystals as claimed in any one of claims 1 to 3, characterized in that: The steps include: Step 1, ingredients: according to the preset total amount and proportion, accurately weigh carbonyl iron with a particle size of 5-8 microns and 250 mesh nanocrystals, and place them in a stainless steel plate for later use; Step 2, dehumidification: Place the container containing the powder in an oven and dry it at 80 degrees Celsius for 60 minutes to completely remove the moisture in the material; Step 3, mixing: the resin is mixed with carbonyl iron and nanocrystalline powder in a certain proportion, and then poured into a mixing barrel; Step 4: Dispersion: Use a stirrer to disperse the mixture and stir for 45 minutes to ensure that all components are evenly mixed to form a uniform absorbing coating material; Step 5: Coating and curing: The prepared absorbing coating material is evenly coated on the aluminum plate by spraying or brushing, and then placed in an oven and dried at 70 degrees Celsius for 60 minutes to complete the curing process.

5. The preparation method according to claim 4, characterized in that: The nanocrystals are obtained by rapid quenching and tempering, including the following steps: Step 1, smelting: according to the ratio, accurately weigh the raw materials of iron, silicon, niobium, boron and copper, add the weighed raw materials into the rapid quenching furnace in order, and carry out high-temperature smelting to ensure that all elements are fully integrated; Step 2, rapid quenching treatment: using the rapid cooling of the rapid quenching furnace, the molten metal liquid is quickly cooled to a solid state to form an amorphous structure; the cooling rate is controlled, when the molten metal liquid is cooled, the atoms or molecules do not have time to arrange according to the conventional crystalline structure, thus forming a disordered, amorphous solid structure; Step 3, making a strip and winding ring: the alloy material after rapid quenching is processed through a specific strip making process to prepare an amorphous alloy strip of a desired shape, and then sent to a winding machine to wind the amorphous strip into an amorphous ring; Step 4, heat treatment: at the crystallization temperature, the atoms or molecules inside the amorphous ring gain energy, rearrange the amorphous structure to transform into nanocrystals, and make the material obtain a hysteresis loop close to a rectangle; the heat treatment method is: first, the temperature is selected within the crystallization temperature range of the material; second, the tempering time must be sufficient to rearrange the atoms or molecules from the amorphous state to the crystalline structure; finally, the amorphous ring is oriented in the tempering furnace and the furnace door is closed to evacuate; at the beginning of heating, the coil of the tempering furnace is powered on to form a magnetic field perpendicular to the radial direction of the amorphous ring; after the furnace temperature rises to the crystallization temperature, it is kept warm for 1 hour, and then all power supplies of the tempering furnace are turned off and naturally cooled to room temperature before being taken out of the furnace; the nanocrystalline rings after being taken out of the furnace are crushed, ball-milled, and sieved to obtain nanocrystalline powder.

Citation Information

Patent Citations

  • Multi-element composite microwave absorbent, microwave absorbing coating, microwave absorbing base material and preparation method

    CN103073961A